NEW-ONSET THYROID EYE DISEASE AFTER COVID-19 VACCINATION: A CASE REPORT - Hi, Jamie Teoh; M, Norlaila; Aw, Norasyikin (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The relationship between autoimmunity and SARS-CoV-2 vaccine has explained how thyroid dysfunction developed following vaccination but the onset of thyroid eye disease (TED) is scarcely described. We report a case of Graves’ disease (GD) developed TED after three weeks of BNT162B2 SARS-CoV-2 vaccine (Pfizer-BioNTech) injection. CASE A 54-year-old non-smoking male presented with new-onset bilateral eyes redness, proptosis, and diplopia three weeks after receiving the second dose of mRNA BNT162B2 SARS-CoV-2 vaccine. He was diagnosed with GD without TED in 2003 and underwent radioactive iodine ablation in 2020. He subsequently developed hypothyroidism and was started on levothyroxine with stable thyroid function test throughout clinic visits. There were no recent stressful events including COVID-19 infection. . On examination, he has bilateral exophthalmos, chemosis, conjunctival injection, swollen eyelids and caruncles, with intact vision. Blood tests revealed normal TSH, free T4, and T3, but elevated TSH-receptor antibodies of 3.60 IU/L (<1.75) and anti-thyroid peroxidase (TPO) antibodies of >600 IU/ml (0-34). MRI orbit showed bilateral extraocular muscle enlargement and proptosis. Intravenous methylprednisolone was given weekly for 12 weeks. There was significant improvement concerning congestive symptoms and diplopia after the third dose of methylprednisolone. Thyroid eye disease is the extrathyroidal manifestation of GD resulting from the autoimmune and inflammatory process. The temporal relationship of the onset of TED after mRNA SARS-CoV-2 vaccination in our case was suggestive, and there were no other inciting events identified. The postulated mechanisms include immune reactivation, molecular mimicry between the SARS-CoV-2 spike proteins and thyroid proteins, and the autoimmune/inflammatory syndrome induced by adjuvants present in the mRNA vaccine. CONCLUSION Patients with autoimmune thyroiditis should be monitored closely after SARS-CoV-2 vaccine as they may develop TED and require treatment.